Could a B-1 Cell Derived Phagocyte Be One of the Peritoneal Macrophages during LPS-Driven Inflammation? - Popi, Ana Flavia; Osugui, Lika; Perez, Katia Regina; Longo-Maugeri, Ieda Maria; Mariano, Mario [UNESP] (Public Library Science, 2012)
The inflammatory response is driven by signals that recruit and elicit immune cells to areas of tissue damage or infection. The concept of a mononuclear phagocyte system postulates that monocytes circulating in the bloodstream are recruited to inflamed tissues where they give rise to macrophages. A recent publication demonstrated that the large increase in the macrophages observed during infection was the result of the multiplication of these cells rather than the recruitment of blood monocytes. We demonstrated previously that B-1 cells undergo differentiation to acquire a mononuclear phagocyte phenotype in vitro (B-1CDP), and we propose that B-1 cells could be an alternative origin for peritoneal macrophages. A number of recent studies that describe the phagocytic and microbicidal activity of B-1 cells in vitro and in vivo support this hypothesis. Based on these findings, we further investigated the differentiation of B-1 cells into phagocytes in vivo in response to LPS-induced inflammation. Therefore, we investigated the role of B-1 cells in the composition of the peritoneal macrophage population after LPS stimulation using osteopetrotic mice, BALB/Xid mice and the depletion of monocytes/macrophages by clodronate treatment. We show that peritoneal macrophages appear in op/op((-/-)) mice after LPS stimulation and exhibit the same Ig gene rearrangement (VH11) that is often found in B-1 cells. These results strongly suggest that op/op((-/-)) peritoneal macrophages are B-1CDP. Similarly, the LPS-induced increase in the macrophage population was observed even following monocyte/macrophage depletion by clodronate. After monocyte/macrophage depletion by clodronate, LPS-elicited macrophages were observed in BALB/Xid mice only following the transfer of B-1 cells. Based on these data, we confirmed that B-1 cell differentiation into phagocytes also occurs in vivo. In conclusion, the results strongly suggest that B-1 cell derived phagocytes are a component of the LPS-elicited peritoneal macrophage population.